Genome-Wide Identification and Expression Analysis of VviYABs Family Reveal Its Potential Functions in the Developmental Switch and Stresses Response During Grapevine Development - Jiu, Songtao; Zhang, Yanping; Han, Peng; Han, Yubo; Xu, Yan; Liu, Gengsen; Leng, Xiangpeng (Frontiers in Genetics, 2022)
The plant-specific YABBY (YAB) transcription factors play multiple roles in plant growth and development process. However, no comprehensive study has been performed in grapevine, especially to determine their roles in berry development and abiotic stress response. A total of seven VviYABs allocating to six chromosomal positions of grapevine were identified and classified into five subfamilies based on phylogenetic and structural analysis. The promoter elements analysis and tissue-specific transcriptional response of VviYABs suggested that VviYABs might play vital roles during plant growth and development. VviYAB1, 2, 3, and 5 showed significantly higher expression levels in vegetative/green organs than in mature/woody tissues, implying that VviYABs might be involved in regulatory switch from the immature to the mature developmental phase. Four VviYAB genes (VviYAB1, 2, 3 and VviFAS) were gradually down-regulated expression during berry developmental and ripening, which can be considered as putative molecular biomarkers between vegetative/green and mature/woody samples and were used to identify key developmental and metabolic processes in grapevine. Furthermore, VviYAB1 and VviYAB3 was significantly increased expression by gibberellic acid (GA3) and N-(2-chloro-4-pyridyl)-N'-phenylurea (CPPU) treatment, suggesting an involvement in fruit expansion by mediating GA3 and cytokinin signaling pathway. Additionally, microarray and RNA-seq data suggested that VviYABs showed transcriptional regulation in response to various abiotic and biotic stresses, including salt, drought, Bois Noir, Erysiphe necator, and GLRaV-3 infection. Overall, our present results will provide better understand the classification and functions of VviYABs during early berry development and in response to abiotic and biotic stresses in grapevine.